Design, synthesis, anti-mycobacterial activity, molecular docking and ADME analysis of spiroquinoxaline-1,2,4-oxadiazoles via [3+2] cycloaddition reaction under ultrasound irradiation - Kanchrana, Madhu; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (MOLECULAR DIVERSITY, 2024)
Keywords: 2; 4-oxadiazoles; cytotoxicity activity; molecular; Mycobacterium tuberculosis; Spiroquinoxaline-1

Ultrasound-assisted ionic liquid-mediated green method for synthesis of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidines, their anti-tubercular activity, molecular docking study and ADME predictions - Baddepuri, Sravanthi; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (New Journal of Chemistry, 2024)
The aim of the study is to develop the synthesis of a novel series of potent anti-tubercular (anti-TB) activity of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidine derivatives via an efficient green approach achieved by using an ionic liquid ([Bmim]BF4) under ultrasonication. The title compounds 4a-4ad with a general molecular formula CaHbX(0-2)NcOd (X = F/Cl/Br) were produced with high yields in shorter reaction time and well characterized by using spectral techniques; and finally single crystal X-ray diffraction method (4b). The newly synthesized compounds were evaluated for their in vitro anti-TB activity against Mycobacterium tuberculosis H37Rv strain. Among all, six compounds 4e (C36H29N5O4), 4g (C34H28N4O3), 4q (C36H28F2N4O2), 4r (C36H28ClFN4O2), 4y (C36H29BrN4O2) and 4z (C36H28BrFN4O2) exhibited significant anti-TB activity with MIC value 6.25 mu g mL-1, when compared to the standard drug ethambutol (MIC:1.56 mu g mL-1). In silico molecular docking studies were performed against M. tuberculosis enoyl-acyl carrier protein reductase inhibitor. The compounds 4o, 4p, 4y and 4aa were exhibited least binding energies -12.58, -12.61, -12.58 and -12.57 kcal mol-1, respectively. These results reveal that the produced compounds might be used for the future generation of novel anti-TB drugs. The study aims to develop and synthesis of a novel series of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidine derivatives as potent anti-TB agents via an efficient green approach by using an ionic liquid ([Bmim]BF4) under ultrasonication.

Green one-pot three component synthesis of thiazolidine-2,4-dione based bisspirooxindolo-pyrrolidines with [Bmim]BF4: their in vitro and in silico anti-TB studies - Rukyanaik, V.; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (Molecular Diversity, 2025)
A simple and effective three-component one-pot green methodology was employed for the synthesis of a new thiazolidine-2,4-dione based bisspirooxindolo-pyrrolidine derivatives using [Bmim]BF4 ionic liquid via [3 + 2] cycloaddition reaction. It is an environmentally benign, column chromatography-free, shorter reaction time, good yield and easy product isolation method. The synthesized compounds 10a-x, were thoroughly characterized by using various spectroscopic methods like FT-IR, H-1 NMR, C-13 NMR, Mass spectrometry and finally by single crystal X-ray diffraction method. In vitro anti-tubercular (anti-TB) activity studies were carried out on these synthesized compounds, and they showed good to moderate anti-TB activity against Mycobacterium tuberculosis H37Rv strain. The compound 10a exhibited good anti-TB activity, with an MIC (Minimum Inhibitory Concentration) value of 12.5 mu g/mL, and the compounds 10m, 10o and 10r showed moderate activity with an MIC value of 25.0 mu g/mL. Remaining compounds exhibited poor activity against Mycobacterium tuberculosis. Ethambutol, rifampicin and isoniazid were used as standard drugs. Furthermore, in silico molecular docking experiments on the TB protein (PDB ID: 1DF7) were carried out to understand the binding interactions, and they showed least binding energy values ranging from -8.9 to -7.2 kcal/mol.
Keywords: 4-dione based bisspirooxindolo-pyrrolidines; Anti-TB activity; green synthesis; Molecular docking; Thiazolidine-2; [3+2] cycloaddition reaction; [Bmim]BF4

An ultrasound-assisted green synthesis of 1,3-diphenyl pyrazole-based spirooxindolo-1,2,4-oxadiazoles: their in vitro anti-tubercular activity and in silico molecular dynamics - Baddepuri, Sravanthi; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Gangarapu, Kiran; Basavoju, Srinivas (Chemistryselect, 2025)
A simple base-mediated one-pot synthetic green methodology has been successfully employed for the synthesis of 1,3-diphenylpyrazole-based spirooxindolo-1,2,4-oxadiazole derivatives. The newly synthesized analogues were tested for their in vitro anti-tubercular activity (anti-TB) against Mycobacterium tuberculosis H37Rv strain, and the results were reported as minimum inhibitory concentration (MIC) values ranging from 3.125 to 25 mu g/mL. Especially, the five compounds 3a, 3f, 3k, 3q, and 3v exhibited good to moderate anti-TB activity with MIC of 3.125 mu g/mL when compared to the reference drug ethambutol (MIC: 1.56 mu g/mL). In silico Molecular docking and molecular dynamics simulations of the protein-ligand complex (3a, 3f, 3k, and 3v) against Mycobacterium tuberculosis DprE1 (PDB ID: 5OEQ) of M. tuberculosis H37Rv strain revealed that these four compounds could be promising anti-mycobacterial candidates, as evident from the binding results and stability of the docked-ligand complexes with considerable least binding energies. ADME parameters were also studied to assess the drug likeness, which clearly shows that the newly developed compounds might be useful for the future development of novel anti-tubercular drugs.
Keywords: 1; 2; 4-oxadiazoles; In silico molecular dynamic studies; In vitro anti-tubercular activity; ultrasonication